Simulated ice thickness, supraglacial debris thickness and velocity for Khumbu Glacier, Nepal, using the iSOSIA ice-flow model - Rowan, Ann (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
Simulated ice thickness (ice, metres), supraglacial debris thickness (dh, metres) and velocity (velocity, metres per year) for Khumbu Glacier, Nepal, produced using the iSOSIA ice-flow model presented in Rowan et al. (in revision, Journal of Geophysical Research-Earth Surface). The files contained in this collection present the outputs from three experiments: Experiment 1, six files, three simulations showing the effect of change in mean annual air temperature to the present day from 1.5 degC to 3.5 degC relative to the Little Ice Age. Experiment 2, four files, two simulations showing the effect of change in the h0 constant describing the reduction in sub-debris melt with debris thickness. Experiment 3, four files, two simulations, showing the effect of change in mean annual air temperature to the present day from 2.5 degC to 3.5 degC relative to the Little Ice Age where h0 = 1.1 m. Results from the optimal simulation, nine files, one simulation, showing results for simulated ice thickness, supraglacial debris thickness and glacier velocity for the Little Ice Age, 1984 CE and 2015 CE. Funding was provided by the NERC grant NE/P00265X/1. : Model outputs were created using the iSOSIA ice-flow model version spm-3.3.3 to simulate the feedback between debris thickness, ice flow and mass balance. This model version is presented and described in detail in Rowan et al. (2015, Earth and Planetary Science Letters; https://doi.org/10.1016/j.epsl.2015.09.004). : iSOSIA ice-flow model version spm-3.3.3 : The glacier model outputs are transient conditions collected from simulations made over longer periods. The higher-order iSOSIA model (Egholm et al., 2011, Journal of Geophysical Research-Earth Surface) was implemented using a 100-m grid spacing and forced by elevation-dependent accumulation and ablation gradients, modified where supraglacial debris was simulated to give a reduction in sub-debris melt equivalent to that found for a positively-skewed distribution of debris thickness (h0 = 1.1 m). For further details of the mass balance scheme, see Rowan et al. (in review, Journal of Geophysical Research-Earth Surface).